The lost and rediscovered holotype of Alyssum austrodalmaticum (Brassicaceae) is in line with the latest taxonomic treatment - Španiel, Stanislav; Rešetnik, Ivana; Buzjak, Suzana (Phytotaxa, 2018)
Alyssum austrodalmaticum was originally described as an endemic species from southern Croatia. It has been considered a dubious taxon because its holotype specimen got lost and because of the scant information contained in the protologue. To settle the interpretation of the name and its application to other Western Balkan populations, a neotype was recently designated. Soon after, the lost holotype specimen was accidentally rediscovered. It is in agreement with the (now superfluous) neotype and the most recent circumscription of the species. Here we present the holotype, summarize the previous uncertainty surrounding this taxon and list all its herbarium specimens from Croatia and adjacent regions deposited in the herbaria CNHM, ZA, ZAHO and ZAGR.